Toward an information and communication technology development in developing countries - Khasawneh, Mohammad M.F.; Ibrahim, Huda (IBIMA Publishing, 2008)
The rapidly development and exceptional growing of Information and Communication Technology (ICT) have continuously affected all aspects of life and activities in the world. ICT becomes a major factor that drives social, economic and human or individual development in one country. Individual who can't accept or use the technology innovation will suffer difficulties to go together with the world especially after a period of time when the innovation becomes an available commodity in the world. In spite of great development of ICT and high acceptance of the technology by organizations and individuals in developed nations, adoption and acceptance of ICT innovations, due to some determinants, are still low in developing countries including the Arab countries. Therefore a study, based on some relevant adoption model, needs to be conducted to understand and further discover about the adoption of ICT in developing countries especially in Arab world. The study includes comparing several adoption and innovation model in a way to identify a viable model for the adoption of technology in Jordan and other similar developing countries. The findings of the study will enhance our knowledge of the adoption and diffusion of ICT by concentration on an area hitherto neglected.